Transcript Profiling of Hevea brasiliensis during Latex Flow - Chao, Jinquan; Yang, Shuguang; Chen, Yueyi; Tian, Wei-Min (Frontiers in Plant Science, 2017)
Latex exploitation enhances latex regeneration in rubber trees. The latex exploitation-caused latex flow lasts from ten minutes to a few hours, which is convenient for exploring the transcript profiling of latex metabolism-related genes at the different stages of latex flow. In the present study, the expression pattern of 62 latex metabolism-related genes involved in water transportation, carbohydrate metabolism, natural rubber biosynthesis, hormone signalling, ROS generation and scavenging, and latex coagulum across three stages of latex flow between rubber tree clones CATAS7-33-97 and CATAS8-79 were comparatively analysed by quantitative real-time PCR. The two clones show differences in latex regeneration and have a different duration of latex flow. The results showed that the expression levels of 38 genes were significantly higher in CATAS8-79 latex than in CATAS7-33-97 during latex regeneration, while 45 genes had a notably higher expression level in CATAS8-79 latex during latex flow. Together with the activation of the MEP pathway and jasmonate pathway in CATAS8-79 latex, HbPIP1;3, HbPIP1;4, HbSUT3, HbSus3, HbHMGS1-2, HbMK should contribute to the high latex regeneration ability. The up-regulation of ethylene signalling and Hb44KD and the down-regulation of latex coagulation-related genes in CATAS8-79 latex might contribute to its longer latex flow duration. This study provides some cues for revealing the regulation of latex metabolism in rubber trees.